Impact of Exaggeration in Advertisement of a Fabric Softener on Product Attractiveness: - Takehiro Ebitani; Takumi Kato (Maketingu rebyu, 2024)
Exaggerations through which product features are excessively highlighted are common in current advertisements. The impact of such exaggerated expressions on consumers perception have been widely discussed. While much of the existing research has focused on the negative consequences of exaggeration, positive effects have been suggested under two conditions: (1) when consumers already hold a favorable attitude towards the brand, and (2) when the national culture is more accepting of exaggeration. However, these studies often rely on consumer attitudes and attributes, and there is a scarcity of discussion on the exaggerated elements that are perceived to be attractive by consumers. Therefore, this study focuses on fabric softener advertisements, identifying fragrance (private benefit) and ethicality (public benefit) as exaggerated elements. Two hypotheses were formulated for the attractiveness of advertisements when each element is excessively emphasized: H1: excessive representation of the fragrance element (personal benefit) in fabric softener advertisements negatively influences the attractiveness of the ad; and H2: excessive representation of the ethical element (public benefit) in fabric softener advertisements positively influences the attractiveness of the ad. The results of a randomized controlled trial supported both hypotheses. Thus, exaggerated expression of the public benefit element enhances the perceived attractiveness of advertisements, suggesting that companies should actively incorporate such elements to enhance consumer perception of ad appeal.